2014
DOI: 10.1038/nrmicro3399
|View full text |Cite
|
Sign up to set email alerts
|

What is a resistance gene? Ranking risk in resistomes

Abstract: Metagenomic studies have shown that antibiotic resistance genes are ubiquitous in the environment, which has led to the suggestion that there is a high risk that these genes will spread to bacteria that cause human infections. If this is true, estimating the real risk of dissemination of resistance genes from environmental reservoirs to human pathogens is therefore very difficult. In this Opinion article, we analyse the current definitions of antibiotic resistance and antibiotic resistance genes, and we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
583
0
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 789 publications
(614 citation statements)
references
References 79 publications
8
583
0
23
Order By: Relevance
“…The distances of both the nearest ARGs and MRGs from the MGEs were much closer in bacteria from pathogen species and human habitat, reflecting the previous reported substantial capacity to develop resistance genes on MGEs in human pathogens (Perry and Wright, 2013;Gillings et al, 2015;Wales and Davies, 2015). Indeed, equipped on the proper transfer machinery, the efficient vehicles in gene shuffling, resistance gene dissemination can markedly be enhanced, benefiting the bacterial communities under environmental stress (Martinez et al, 2015;Soucy et al, 2015). Characterized by long exposure to selective pressure from antimicrobial and non-antimicrobial agents in human habitat, massive genetic exchanges have conferred efficient defense system to specific bacterial lineages (Jernberg et al, 2010;Juhas, 2015).…”
Section: Transfer Potential Of Args and Mrgssupporting
confidence: 55%
See 1 more Smart Citation
“…The distances of both the nearest ARGs and MRGs from the MGEs were much closer in bacteria from pathogen species and human habitat, reflecting the previous reported substantial capacity to develop resistance genes on MGEs in human pathogens (Perry and Wright, 2013;Gillings et al, 2015;Wales and Davies, 2015). Indeed, equipped on the proper transfer machinery, the efficient vehicles in gene shuffling, resistance gene dissemination can markedly be enhanced, benefiting the bacterial communities under environmental stress (Martinez et al, 2015;Soucy et al, 2015). Characterized by long exposure to selective pressure from antimicrobial and non-antimicrobial agents in human habitat, massive genetic exchanges have conferred efficient defense system to specific bacterial lineages (Jernberg et al, 2010;Juhas, 2015).…”
Section: Transfer Potential Of Args and Mrgssupporting
confidence: 55%
“…Therefore, by examining ARG-MRG coupling profile, we were prompted to ascertain whether there is a significant genome grouping pattern by ecologies. Co-occurrence of antibiotic and metal resistance genes L-G Li et al A significant genome cluster by habitats was observed (P-value o0.001, ANOISM; Supplementary Figure S8), suggesting that although interhabitat resistance gene transfer has frequently been detected (Martinez et al, 2015), these events have not homogenized the ARG-MRG coupling pattern among human, soil and water habitats. Instead, other ecological features among habitats might have a more substantial effect in shaping the resistome.…”
Section: Co-occurrence Between Args and Mrgsmentioning
confidence: 99%
“…However, the less contribution of HGT through MGEs should not be overlooked, it should be emphasized instead, because the spread of ARGs through HGT had much higher risks than evolution of bacterial community (Martínez et al, 2015). The less contribution of MGEs might just indicate that the HGT through MGEs was not enough to obscure the significant correlation between evolution of ARGs and changes of bacterial community composition during sludge bio-drying.…”
Section: The Variation Of the Contributors To The Evolution Of Argsmentioning
confidence: 99%
“…In recent years, the antibiotic resistome from both environmental and host-associated microbiomes has been explored (either function-or sequence-based), leading to the discovery of numerous ARGs (8,(12)(13)(14)(15). However, the risk of these identified ARGs has been considered to be overestimated because most studies have failed to differentiate between intrinsic ARGs and mobile ARGs (16). The mobile ARGs that are frequently as-sociated with mobile genetic elements (MGEs) and disseminated by HGT have been considered to have the highest risk of developing resistance among the antibiotic resistome (16).…”
mentioning
confidence: 99%
“…However, the risk of these identified ARGs has been considered to be overestimated because most studies have failed to differentiate between intrinsic ARGs and mobile ARGs (16). The mobile ARGs that are frequently as-sociated with mobile genetic elements (MGEs) and disseminated by HGT have been considered to have the highest risk of developing resistance among the antibiotic resistome (16).…”
mentioning
confidence: 99%